CENTRAL ASIA AND THE SOUTHERN CAUCASUS: EGIONAL SECURITY IN THE NEW WORLD ORDER - MALYSHEVA, Dina (CENTRAL ASIA AND THE CAUCASUS, 2004)
Recently, the American and Russian presidents have been repeatedly confirming their resolution to move toward a new strategic partnership in order “to meet together the challenges of the 21st cen-tury.”1 But these relations have still not been raised to the level of an alliance for several reasons:he disagreements on the Iraqi issue; American concern over the trends toward curbing democracy in Russia (“in Russia capitalism triumphed while democracy was defeated”2 ); the YUKOS case and arrest of its head Mikhail Khodorkovskiy; Russia’s policies in Georgia, Moldova, and Ukraine, which many in America perceive as “aggressive,” etc. The numerous recommendations by the American “hawks” and certain members of the Bush Administration to pursue a harsher policy toward Russia are creating the impression that the United States wants to squeeze Russia out of its traditional zone of interests and the settlement process of the post-Soviet conflicts. Russia is suspicious of the EU’s enlargement. The doubts remained even after Russia reached an agreement with the EU leaders on the Iraqi crisis in the spring of 2003. Moscow is responding nervously to any changes in the international security system: NATO’s movement eastward; U.S. military bases in Central Asia; the growing presence of NATO and the U.S. in the Southern Caucasus; Washington’s plans to use military force to guard the Azeri sector of the Caspian, the Caspian pipeline systems, etc. The Russian political establishment cannot ignore the consistent efforts to squeeze Russia out of its tradition-al spheres of influence in the Far and Near abroad, as well as the direct interference in the domestic affairs of the formally independent CIS countries to topple the regimes the U.S. and NATO find objectionable (at first in Georgia, and then in other countries). Under this pressure Russia is hastily readjusting its foreign policy strategy. The “lost positions in the CIS” is a pet subject of the Russian critics of Atlanticism who are out to find an enemy in the United States. They were enraged by Moscow’s support for the U.S.-led antiterrorist operation in Afghanistan. Certain political forces are putting pressure on the Russian leaders in order to force them, the president in the first place, to compete with U.S. military might, its defense funding, and the money poured into military operations outside the United States. On the other hand, some of the politicians and members of the expert community warn against spoiling relations with the West. They suggest that the country should promote its own economic and political interests by using its geographic proximity to the post-Soviet South and the traditional ties with it. The public in the West is equally concerned about the recently revealed strategic rivalry with the Kremlin and the anti-Russian rhetoric that appears more and more frequently in political statements and the media. The relations between the U.S. and the EU are not simple either. Its members (with the exception of the U.K., the traditional American ally) betray no readiness to promote American interests in the CIS members. They would rather pursue their own policy and object, in particular, to simultaneous containment of Russia, Iran, and China in southern Eurasia.